Clot characterization by multidisciplinary approach: biochemical and imaging parameters in a hypocoagulative setting. A pilot study. - Francesco Marongiu; Dimitrios Marco Ntoukas; Luigi Barberini; Maria Filomena Ruberto; Maria Sebastiana Piras; Maria Conti; Maria Luisa Di Martino; Mario Mura; Silvia Marongiu; Maria Luigia Vannini; Mattia Lillu; Monica Piras; et al. (SAGE Publishing, 2021)
Background: Clot characterization is, to the present days, a multimodal approach: scanning the clot by electron microscopy (SEM) is helpful for the visualization of fibrin structure along with laboratory parameters such as the clot waveform analysis (CWA) and thrombin generation in different settings of clot abnormalities. This study aimed to assess whether the coagulative parameters were consistent with the clot images texture acquired by SEM, and therefore to propose a more generalist and integrative approach to clots classification. Design and Methods: In this pilot study, the examined population consists of eight healthy subjects, seven patients affected by Acquired Hemophilia A (AHA) and seven patients treated with Vitamin K Antagonists (VKAs), similar for age and gender. We studied the velocity and acceleration (1st and 2nd derivative of the aPTT) of clot formation (CWA), the thrombin generation, and the clots' scanning by SEM. Images acquired with SEM were then analyzed with the MATLAB software with the "Texture Analysis" methods to perform classification. Among the various texture parameters, we reported Contrast and Energy. Results: Significant differences among healthy subjects, patients with AHA and those treated with VKAs were detected for the coagulative parameters. We found no differences between VKAs and AHA patients. Contrast and energy highlighted a significant difference among the three groups in agreement with the laboratory's parameters. We found no significant differences between VKAs and AHA patients. Conclusions: The use of SEM, CWA and thrombin generation parameters may be a starting point for studies aimed to demonstrate the general characteristics of clot formation in different clinical conditions with a multiparametric approach.